Rebuilding disrupted supply chains: How can a self-organised social group facilitate supply chain resilience? - Lusiantoro, Luluk; Pradiptyo, Rimawan (Emerald Publishing, 2022)
Purpose: This paper seeks to explore how a self-organised social group (SOSG) can facilitate supply chain resilience (SCRES) during an emergency condition. Design/methodology/approach: A netnographic research was conducted on SONJO, an online SOSG emerging in response to problems in personal protective equipment (PPE) and food small businesses' supply chains (SCs) during the state of COVID-19 emergency in Yogyakarta, Indonesia. Qualitative data of 237,010 words were extracted from the group chats among 223 SONJO WhatsApp Group (WAG) members and were analysed using template analysis. Findings: This paper reveals five communicative acts through which the SOSG facilitates SCRES, namely supply chain (SC) knowledge sharing, networking, bridging, mapping, and mindfulness. The enactment of these communicative acts could foster SC collaboration and help rebuild and sustain the SC operations during the critical period of the pandemic. The SOSG also facilitates the SC actors to be heedful of their responsive actions and risky operations. Practical implications: This paper emphasises the need for organisations to build and maintain relationships with social communities and to extend their social capital beyond their existing SC linkages as an alternative way to survive unexpected disruptions. Originality/value: This paper offers a novel perspective to understand SCRES from an external force. It proposes that, in the face of a devastating disruption, SCRES is not a self-induced process and that the SOSG could play a pivotal role in rebuilding the disrupted SCs. It also shows how a humanitarian effort could help rebuild commercial SCs. © 2022, Emerald Publishing Limited.